POTENSI HUMAN EMBRYONIC STEM CELL-DERIVED RETINAL PIGMENT EPITHELIUM SEBAGAI AGEN TERAPI REGENERATIF DRY AGE RELATED MACULAR DEGENERATION - Winarta, Sanjaya; Kurnia, Karen; Mundi, Gabriella Novelin (Essence of Scientific Medical Journal; Vol 20 No 2 (2022): Volume 20 No. 2 (Juli - Desember 2022) Essential: Essence of Scientific Medical Journal, 2023)
Introduction : Age related macular degeneration (AMD) is one of degenerative eye disease in the elderly group due to degeneration of the retinal pigment epithelium layer (RPE). This degeneration leads to photoreceptor cells loss. AMD is the leading cause of blindness in developed countries and third globally. There are two types of AMD, wet and dry AMD. So far, there are no any proven treatments exist for dry AMD. Therefore, novel treatment for dry AMD is still needed. Discussion : Five major studies correlated to the aims of this literature review stated that hESCs-RPE had the potential to become regenerative treatment for RPE. The use of this stem cells could increase the pigmentation of retina that could be assessed through funduscopy and optical coherence tomography (OCT). This indicated an improvement in the patient’s retinal pigment epithelium. Furthermore, there was also an improvement in visual acuity without any signs of teratoma, acute rejection reaction, or post-transplantation infection. Conclusion : The use of hESCs-RPE could be the inovation treatment of dry AMD.